Electronic cigarettes: a survey of users - Etter Jean-François (BMC, 2010)
Abstract Background Little is known about users of electronic cigarettes, or their opinions, satisfaction or how and why they use such products. Methods An internet survey of 81 ever-users of ecigarettes in 2009. Participants answered open-ended questions on use of, and opinions about, ecigarettes. Results Respondents (73 current and 8 former users) lived in France, Canada, Belgium or Switzerland. Most respondents (77%) were men; 63% were former smokers and 37% were current smokers. They had used e-cigarettes for 100 days (median) and drew 175 puffs per day (median). Participants used the ecigarette either to quit smoking (53 comments), to reduce their cigarette consumption (14 comments), in order not to disturb other people with smoke (20 comments), or in smoke-free places (21 comments). Positive effects reported with ecigarettes included their usefulness to quit smoking, and the benefits of abstinence from smoking (less coughing, improved breathing, better physical fitness). Respondents also enjoyed the flavour of ecigarettes and the sensation of inhalation. Side effects included dryness of the mouth and throat. Respondents complained about the frequent technical failures of ecigarettes and had some concerns about the possible toxicity of the devices and about their future legal status. Conclusions Ecigarettes were used mainly to quit smoking, and may be helpful for this purpose, but several respondents were concerned about potential toxicity. There are very few published studies on ecigarettes and research is urgently required, particularly on the efficacy and toxicity of these devices.